Pengaruh Air Gambut Terhadap Karakteristik Marshall Pada Campuran Asphalt Concrete - Binder Course (AC-BC) Yang Menggunakan Abu Tandan Sawit Sebagai Bahan Pengisi (Filler) - Khairil Badry; Alfian Malik; Yosi Alwinda (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The use of fillers is useful for filling empty voids in the asphalt mixture for highway pavements so that the use of fillers greatly affects the strength of its stability. Materials that can be used as fillers are those that have pozzolanic content and contain high levels of silica. One of the materials that has this content is palm bunch ash. The water content of peat has a high acidity, so it can damage a pavement when there is inundation for a long time. The purpose of this study was to determine the effect of peat water on the characteristics of marshall in AC-BC mixture which uses oil palm bunch ash as a filler. This study used a percentage of filler variations in the form of 0%, 2%, 4% and 6% which were immersed for 0.5 hours, 3 hours, 6 hours, 12 hours and 24 hours using peat water. This study follows the Standard Specification of Bina Marga 2018. In this study, the KAO value obtained the highest stability value and 4% filler variation at 0.5 hour immersion time of 906.53 kg and the lowest stability value of 0% filler variation at 24 hours immersion time of 505.33 kg. then for the IKS value that meets the standard requirements of the Standard Specification of Bina Marga 2018 only at 3 hours of immersion time for all percentages of filler variations where the maximum requirement for reduction in the stability value is 90% from the original stability value. Keywords: Peat water, AC – BC, filler, Palm Bunch Ash